Segulung Era, Sepetak Lahan - Kadek Agung Arya Krisna Kusmawa; Ida Ayu Wimba Ruspawati; I Ketut Sutapa (Jurnal IGEL : Journal Of Dance, 2026)
Work of Dance The 'Segulung Era, Sepetak Lahan' A Written Report and Presentation For Choreography Major Indonesian Institute of the Arts Denpasar Independent Study Program/Project 2025 By: Kadek Agung Arya Krisna Kusmawa This research focuses on the creation of a contemporary dance work titled "Segulung Era, Sepetak Lahan", which addresses social and cultural issues related to the shrinking agricultural land in Bali, particularly concerning the Sukawati Tobacco. The phenomenon of land contraction is driven by modernization and the development of the tourism sector, which leads to the conversion of agricultural land into commercial areas. This dance work aims to raise public awareness about the importance of preserving local agricultural culture and maintaining traditional cultural heritage amidst the forces of modernization. The creative process of this dance work utilizes the Collaborative Creation Method developed by Teater Garasi Yogyakarta, which includes stages of Locating the Question, Sourcework, Improvisation, Codification, Composition, and Presentation. Through this work, the author seeks to encourage the younger generation to revisit and preserve local agricultural culture, particularly the Mako Sukawati tobacco, which is increasingly eroded by globalization. Keywords: Sukawati Tobacco, Land Shrinking, Modernization, and Cultural Preservation.